Five structural genes required for ceramide synthesis in Caulobacter and for bacterial survival. (25th October 2020) - Olea‐Ozuna, Roberto Jhonatan; Poggio, Sebastian; EdBergström,; Quiroz‐Rocha, Elva; García‐Soriano, Daniela A.; Sahonero‐Canavesi, Diana X.; Padilla‐Gómez, Jonathan; Martínez‐Aguilar, Lourdes; López‐Lara, Isabel M.; Thomas‐Oates, Jane; Geiger, Otto
Summary: Sphingolipids are essential and common membrane components in eukaryotic organisms, participating in many important cellular functions. Only a few bacteria are thought to harbour sphingolipids in their membranes, among them the well‐studied α‐proteobacterium Caulobacter crescentus, a model organism for asymmetric cell division and cellular differentiation. Here, we report that C. crescentus wild type produces several molecular species of dihydroceramides, which are not produced in a mutant lacking the structural gene for serine palmitoyltransferase ( spt ). Whereas growth of a spt ‐deficient mutant and wild type are indistinguishable during the exponential phase of growth, survival of the spt ‐deficient mutant is much reduced, in comparison with wild type, during stationary phase of growth, especially at elevated temperatures. The structural gene for spt is located within a genomic cluster, comprising another 16 genes and which, like spt, are important for fitness of C. crescentus . Mutants deficient in genes linked to spt by high cofitness were unable to produce dihydroceramide or to survive in stationary phase of growth at elevated temperatures. At least five structural genes are required for dihydroceramide biosynthesis in C. crescentus and sphingolipid biosynthesis is needed for survival of this bacterium and the integrity of its outer membrane.